Effect of particle size and type on asphalt-filler mastic properties and stone mastic asphalt (SMA) performance - Aburkaba, Eltaher Elzarroug (2012)
Stone Matrix Asphalt (SMA) is a gap-graded hot mixture that has higher proportion of coarse aggregate, lower proportion of middle-size aggregates, and higher proportion of mineral filler than conventional mixture. Because of the high quantity of mineral filler (8-12%), the type and size of this fraction should play a major role in the properties of these mixtures and their mastics. A great deal of research has been reported on mineral fillers in the past, however, very little information is available regarding the effect of filler particle size (gradation) and type on the characteristics,viscoelastic properties of asphalt-filler mastics, and mixture properties. This study presents a laboratory investigation into the effects of different fillers on properties of asphalt-filler mastics and SMA mixtures. The fillers physical and chemical properties were characterized using imaging techniques and traditional mechanical testing. Four filler types and three filler particle size (passing the 75, 75/20, and 20 micron sieve) were used to obtain the master curves of mastics and to characterize the stiffening effect of filler particle size and type in mastics using new testing techniques being developed within the SHRP program for testing asphalt binders using the Dynamic Shear Rheometer (DSR) in accordance with AASHTO T315 at different temperatures. The effects of filler on the characteristics of SMA mixtures were also investigated in accordance with AASHTO and ASTM standards. The properties of SMA mixtures evaluated include optimum asphalt cement (AC) content, indirect tensile strength (IDT), Permanent deformation (Rutting), and tensile strength ratio (TSR). The filler particle size distribution and filler type have been found to have a significant influence on asphalt-filler mastics, and the mechanical properties of SMA mixtures. Fillers with medium size particles (50/50 proportion passing 75/20 micron) tend to behave in the most predictable manner. However, the inconsistent trends were observed when the fillers are finer than 20 micron, or when the fillers are coarser (75 micron) and lacking material finer than 20 micron. The filler type has a definite effect on asphalt binder, mastic, and mixture properties; each filler type differs in the amount of property enhancement and performance characteristic. The test data and observations revealed that the combination of coarse to medium size particles had the highest impact on asphalt-filler mastics and SMA mixture properties. They generally performed better than the fine particle size alone (passing the 20 micron sieve) in improving the engineering properties of SMA mixtures and providing resistance against permanent deformation and fatigue cracking while the fine particle size showed better resistance to moisture induced damage than the other two fractions.